Improvement of the sepsis survival rate by adenosine 2a receptor antagonists depends on immune regulatory functions of regulatory T-cells - Zhang, Teng; Zhao, Jie; Fu, Jingnan; Chen, Guibing; Ma, Tao (Frontiers in Immunology, 2022)
Adenosine shows a significant immunosuppressive effect in sepsis via binding to the adenosine 2a receptor (A2aR). Both genetic deletion and pharmacological inhibition of the A2aR may improve survival in sepsis. However, available research on this protective mechanism is quite limited. We used an A2aR antagonist (ZM241385) to treat a cecal ligation and puncture model of normal mice or regulatory T-cell (Treg)-depletion mice and found that the protective effect of ZM241385 is dependent on Tregs. Mechanically, A2aR inactivation was associated with decreased frequencies and reduced function of Foxp3+ Tregs, as evidenced by Foxp3 and CTLA-4 expression and classical effector T-cell proliferative assays, suggesting Treg modulation is a potential protective mechanism against sepsis. Simultaneously, the function and quantity of abdominal neutrophils were improved with ZM241385 treatment. To see if a link exists between them, Tregs and neutrophils were co-cultured, and it was found that ZM241385 blocked the inhibitory effect of Tregs on neutrophils. According to our research, Tregs play a key role in how A2aR antagonists improve sepsis prognosis and bacterial clearance.